Lecciones de la historia económica de Chile: hacia reducir la desigualdad - estructural a partir de una aproximación estadística - Vergara Perucich, José Francisco. (Ariadna, 2021)
Income inequality in Chile has remained constant, with slight variations and which have not been sustained over time. Since 1865, the coefficient to measure inequality averages 0.54; which is high and although in recent years a reduction in inequality has been detected, the structural problem does not allow optimism to feed. Even less after the recent events that take place in the social outbreak of October 2019, when citizens have shouted that they can no longer cope with injustices due to this phenomenon. Based on a statistical analysis, this article prepares a study of the economic factors that most affect the reduction of the inequality coefficient (Gini) in order to identify effective mechanisms to reduce it. The econometric techniques of principal component analysis and multiple linear regression are used to determine the variables that most influence inequality. The results indicate that the role of the State on the economy is relevant to reduce inequality. On the other hand, the specific factors that are most efficient in their reduction are studied and remunerations, urbanization processes and the price of copper are identified as such. By way of conclusions, the need to complement this analysis with qualitative historical studies is reflected and the need to break the methodological fence of the economic sciences in Chile, to reintegrate into the social sciences and contribute to the production of useful knowledge for the production of public policies against structural inequality.
Lessons from the economic history of Chile: towards reducing structural inequality from a statistical approach
Keywords: inequality; Historia económica; Rentas; Pobreza